Sunburst Arc Magellan/MagE observations - Thøger Emil Rivera-Thorsen; Bayliss, Matthew; Jane R. Rigby (Stockholm University, 2019)
These are raw data files from the Magellan telescopes, MagE
spectrograph, that are used in Rivera-Thorsen et al. 2019 (Science). All individual science integrations are included, as well as all the calibration frames: blueflat, redflat, bias, ThAr lamps, order definition flats, and flux calibration stars. Directories include data from three observing runs; the directory name gives the month and year the observations were obtained. All observations are of the galaxy known as the "Sunburst Arc", discussed in Rivera-Thorsen et al. 2019.

The slit positions are as follows:- Img 1 / slit H-9 from August 2018
- Img 5 / slit "1" from May 2017
- Img 8 / slit H-2 from April 2018
- Img 10 / slit H-6 from April 2018
- No LyC slit H-3 from April 2018

Viewing the data: Data is stored in the Flexible Image Transport System (FITS) file format[¹], which is designed to store table or binary image data together with an ASCII header containing meta-data stored as a keyword-value pairs, of which some are mandatory and some are optional.
Multiple software applications exist which can view and analyze FITS files. We recommend either DS9[²], QFitsView[³] or Ginga[⁴] packages, all of which are open source and freely available for both Windows, Mac OS X and GNU/Linux.
Unpacking: The data is compressed in the .tar.gz format, which is natively supported on Mac OS X and GNU/Linux. On Windows, it can be opened with e.g. the 7-Zip software[⁵].
-------------
[¹]: https://en.wikipedia.org/wiki/FITS[²]: http://ds9.si.edu/site/Home.html[³]: http://www.mpe.mpg.de/~ott/dpuser/qfitsview.html[⁴]: https://ejeschke.github.io/ginga/
[⁵]: https://www.7-zip.org/
Keywords: Astrophysics; 20103 Cosmology and Extragalactic Astronomy; Extragalactic Astronomy; Interstellar and Intergalactic Matter; Astronomy, Astrophysics, and Cosmology; Astronomi, astrofysik och kosmologi